Sexual Dysfunction in Patients With Urinary Bladder Stones but no Bladder Outlet Obstruction - Gong, Zhi-Cheng; Wu, Zhi-Liang; Wen, Yao-An; Zou, Jie-Peng; Wang, Xisheng; Leng, Xiaoyan; Bleyer, Anthony J.; Deng, Chunhua; Feloney, Michael P.; Zhang, Yuanyuan; Zhao, Shan-Chao (Frontiers in Medicine, 2021)
Objective: To explore the correlates of sexual dysfunction and lower urinary tract symptoms (LUTS) in male patients with urinary bladder stones and to determine the effect of stone extraction on recovery of sexual function. Materials and Methods: A total of 87 male patients with primary bladder stones were studied from January 2015 to May 2016. All patients underwent pneumatic lithotripsy for bladder stones. Sexual dysfunction was assessed based on sexual function assessment scales. The relationship of bladder stones with sexual dysfunction or LUTS was assessed using a two-sample t-test. Postoperative improvement of sexual function was assessed by repeated measures Analysis of Variance (ANOVA). Results: Forty-one patients had primary bladder stones and 46 had secondary stones from the kidneys. Eighty-three of 87 patients (95%) had sexual dysfunction; 79 patients (91%) had both sexual dysfunction and LUTS. There was a significant association between bladder stones and sexual dysfunction, between sexual dysfunction and LUTS, and between bladder stone and LUTS (p < 0.05). There was no significant association between the course of illness, size and number of bladder stones, or urinary tract infection with sexual function (p > 0.05). In addition, among 83 patients with both bladder stone and sexual dysfunction, 61 patients (73%) had benign prostatic hyperplasia (BPH) and 22 patients (27%) had no BPH. On postoperative evaluation at 3 months, sexual dysfunction scores were significantly improved in 77 patients (88.5%) Conclusion: Patients with bladder stones have a high incidence of sexual dysfunction, particularly those with co-existing LUTS and BPH. About 1/3 patients without BPH had sexual dysfunction and surgical removal of bladder stones significantly improved sexual function and LUTS.